PERBEDAAN HASIL BELAJAR MELALUI MODEL DISCOVERY LEARNING DAN PROBLEM BASED LEARNING - Resyi A. Gani; Wawan Syahiril Anwar; Syahrizal Aditiya (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
DIFFERENCES OF LEARNING OUTCOMES THROUGH THE DISCOVERY LEARNING MODEL AND PROBLEM BASED LEARNINGThis study aims to determine the differences in learning outcomes in the sub-diversity of living things in my environment through discovery learning models and problem-based learning models class IV-A and IV-B in SD Negeri Bojongrangkas 01 school year 2019/2020. This type of research is a comparative experimental research. The study population was class IV-A students using discovery learning models and class IV-B using models based learning. The research instrument was in the form of question sheets. Question sheets are used to measure learning outcomes by using discovery learning models and problem based learning models. The results of the study of the error data normality test using discovery learning models are Lhitung 0.109 Ltable 0.138, while the problem-based learning model is Lhitung95 0.095 Ltable 0.138, meaning that samples are obtained from normal sources. Homogeneity variance test has the criteria in testing Ha is accepted if F2count ≤ F2table on the tarat significant α = 0.05. The results of the research from the variance homogeneity test are F2count 1.04 ≤ F2table 1.69 which states homogeneous. The N-Gain results on the learning discovery models 68, while the problem based learning models 55, there is value tcount 4.28406 ttable 1.99006. So the study concluded that there are differences in learning outcomes in the subtheme of the diversity of living things in my environment through the discovery learning model and problem based learning at SDN Bojongrangkas 01, the discovery learning models is more effective than the problem based learning models.